Effects of different cooking methods on chemical compositions, in vitro starch digestibility and antioxidant activity of taro (Colocasia esculenta) corms. (17th May 2022) - Kapcum, Chutikarn; Pasada, Kannika; Kantiwong, Pearploy; Sroysang, Buraporn; Phiwtawee, Jiratchaya; Suphantharika, Manop; Belur, Prasanna D.; Agoo, Esperanza Maribel G.; Janairo, Jose Isagani Belen; Wongsagonsup, Rungtiwa
Summary: The impacts of different cooking methods (boiling, steaming, baking, microwaving and frying) on chemical compositions, starch digestibility and antioxidant activity of taro corms were investigated. Compared with raw taro, boiling and frying reduced crude protein and ash contents. Frying significantly increased crude fat and fibre contents but decreased carbohydrate content. All cooking methods reduced oxalate content, especially frying. Among the cooked products, the boiled taro had the highest rapidly digestible starch (RDS) but the lowest resistant starch (RS) contents. In contrast, the fried taro provided the lowest RDS but the highest RS contents. All cooking methods reduced the total phenolic content and antioxidant activity of taro. The boiled taro had the lowest antioxidant activity but the fired taro provided the highest. Frying was able to retain most of the health‐promoting compounds with the lowest oxalate content; however, the high consumption of high‐fat fried taro may adversely affect human health. Abstract : Different cooking methods had significant effects on the proximate, oxalate, starch fractions and total phenolic contents of taro. Frying was able to retain most of the health‐promoting compounds with the lowest oxalate content.